Jump squat vs. resisted sprint training programs applied to elite youth soccer players: effects on sprint and power-related performance - Loturco, I.; Pereira, L. A.; Mercer, V. P.; Oliveira, L. P.; Zanetti, V.; Lima, L.; Bastos, T.; Moura, T. B. M. A.; McGuigan, M. R. (The Journal of Strength and Conditioning Research, 2024)
This study examined the effectiveness of 2 different and widely used training programs on the sprint and power-related performance of youth soccer players. Two distinct training strategies—vertically oriented jump squats (JSs) or horizontally oriented resisted sprints (RSs)—were executed under the same absolute loading conditions (i.e., 30% of the athletes` body mass [BM]) during a 4-week preseason period. Training schemes, loading intensities (based on %BM), and the number of experimental sessions were designed in conjunction with the soccer club`s coaching staff, considering the calendar, available resources, and regular training programs. Twenty-five under-17 soccer players performed a series of speed, power, and jump tests before and after 10 resisted training sessions, consisting solely of loaded JS or RS. Overall, neither group (i.e., JS or RS training groups) exhibited any improvement in linear sprint and change-of-direction (COD) speed. Conversely, vertical jumping ability and peak velocity in the loaded JS increased significantly only in the JS group, which may positively affect players` performance and training prescription during short soccer preseasons. Given the challenges in enhancing sprint speed among soccer players during preseasons (and even over the competitive season), coupled with the limited effectiveness of RS in improving sprinting, COD, and jumping capabilities within congested and short training phases (i.e., =4 weeks), the regular use of RS training methods during these phases may be highly questionable. Coaches should carefully consider these critical limitations and potential disadvantages when designing neuromuscular training programs for soccer players during the preparatory phases of the annual training season.